Grasp and dexterous manipulation of multi-fingered robotic hands: a review from a control view point. (18th October 2017) - Ozawa, Ryuta; Tahara, Kenji
Graphical Abstract: Abstract: Manipulation is one of the most important fields in robotics. Nevertheless, even given the long history of manipulation research, technologies for multi-fingered robotic hands are still in development. This paper investigates past research studies on control systems of multi-fingered robotic hands for grasping and manipulation.